Corrosion Analysis of Oil Drilling Pipes On Mobile RIG 42.3 N1500 E In Prabumulih - Elfidiah, Kiagus Ahmad Roni, Agustriono (Faculty of Engineering, Universitas Lampung Jl. Soemantri Brojonegoro No.1 Bandar Lampung, Indonesia 35141, 2020)
In the oil, gas, and geothermal drilling industry, the use of drill pipe is very important to increase the length of the drilling depth. Problems that are often encountered in drilling pipes such as broken, bent, and leaking drilling pipes, one of which is caused by corrosion. Corrosion is the degradation of materials (usually metals) due to the electrochemical reaction of these materials with their environment. This study uses a specimen of carbon steel pipe type G105 where this pipe is used in field drilling. From the results of research on the corrosion rate test, the corrosion rate value is obtained in mm / month. This study took the first drill pipe sample starting from May 2018 to October 2019 with the same sample code with a sample size of 69 pipes. Based on the research results, the largest corrosion rate value in the drilling pipe from May 2018 to October 2019 is 0.12 mm / month. In the research, the smallest remaining life of the drilling pipe is 6.2 months. Of the 69 drilling pipes studied, there were 11 drilling pipe samples that had decreased quality to class 2. Based on the results of Scanning Electron Microscopy photos, the condition of the pipe surface morphology after corrosion and there was surface damage after corrosion.